Characterization of Cucurbit Yellow Stunting Disorder Virus Associated with Yellowing Disease of Watermelon in Saudi Arabia - H. Ahmad; M. A. Al-Saleh; I. M. Al-Shahwan; M. T. Shakeel; Y. E. Ibrahim; M. A. Amer (Journal of Animal and Plant Sciences, 2020)
During the spring season of 2014, watermelon leaves were exhibiting yellowing, mottling and stunting symptoms in Western and Southwestern regions (Jeddah, Al-Lith, Jezan, Asfan, Ghonfada, Tofeel, Wadi Baish, Abu Arish), Saudi Arabia. One hundred thirty-nine samples were collected from symptomatic and asymptomatic watermelon plants. DAS-ELISA was performed to detect Cucurbit yellow stunting disorder virus (CYSDV) and other suspected cucurbit viruses. The obtained results revealed that out of 139 watermelon samples, nine and 98 samples were found to be positive with CYSDV and WmCSV, respectively and 22 samples were found to have mixed infection for both viruses. While no reaction was detected with, any of the other antisera tested against. Approximately 465 bp product were amplified by RT-PCR when CYSDV-Partial heat shock protein (HSP70) specific primer were used with ELISA positive symptomatic watermelon samples. Dot blot hybridization was also performed to detect CYSDV in the samples using CYSDV specific cDNA probe. Asymptomatic plant did not react when RT-PCR and dot blot hybridization assay were used. Partial HSP70 sequences of four CYSDV isolates were determined. When these HSP70 sequences were compared with other CYSDV isolates reported worldwide, the highest identity was between CYSDV KSA isolates (33-CYSDVKSA, 36-CYSDVKSA) and isolate from Portugal. Lowest identity was found between (34-CYSDVKSA, 35-CYSDVKSA), four Spanish isolates and one isolate from each USA and Lebanon. This is the first comprehensive study involving this virus in different regions in Saudi Arabia.
Keywords: Cucurbit yellow stunting disorder virus; immunoblot and indirect enzyme-linked immunosorbent assay; reverse-transcription polymerase chain reaction; Partial heat shock protein